Association of atrial fibrillation and atrial flutter with sick sinus syndrome: a review of the issue based on examples of clinical observations - O. Yu. Schmidt; D. Ye. Volkov; M. S. Brynza; К. H. Uvarova; D. Yu. Pavlova (Zaporožskij Medicinskij Žurnal)
Despite significant progress in the treatment of patients with cardiac arrhythmias, atrial fibrillation (AF) remains one of the leading causes of serious cardiovascular events around the world. Currently, radiofrequency ablation (RFA) is the first-line method in the treatment of patients with AF. However, signs of sick sinus syndrome (SSS) are found in some AF patients after RFA, which requires urgent or planned pacemaker implantation.